2005
DOI: 10.1016/j.orthres.2004.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Less systemic cytokine response in patients following microendoscopic versus open lumbar discectomy

Abstract: The magnitude of the tissue damage from surgery impacts the trauma response. This response is proportional to the severity of surgical stress. Systemic cytokines are recognized as markers of postoperative tissue trauma. Microendoscopic discectomy (MED) recently has become popular for treating lumbar disc herniations, and is associated with favorable clinical outcomes compared with open discectomy (OD). This study postulates that MED is a less traumatic procedure, and therefore has a lower surgical stress respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
4
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(142 citation statements)
references
References 16 publications
6
131
4
1
Order By: Relevance
“…Measuring various serum markers of tissue trauma such as C-reactive protein and systemic cytokines after microendoscopic versus open lumbar discectomy and decompression procedures demonstrates that microendoscopic surgery is associated with a lower level of inflammatory parameters, suggesting decreased invasiveness. 5,13,22,23 Since 2004, we have exclusively used tubular retractors for 1-and 2-level microscope-assisted decompressive surgery in the lumbar spine. In this study, we summarized our clinical results in 230 consecutive patients treated for lumbar disc herniations, lumbar spinal stenosis, and lumbar facet joint cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring various serum markers of tissue trauma such as C-reactive protein and systemic cytokines after microendoscopic versus open lumbar discectomy and decompression procedures demonstrates that microendoscopic surgery is associated with a lower level of inflammatory parameters, suggesting decreased invasiveness. 5,13,22,23 Since 2004, we have exclusively used tubular retractors for 1-and 2-level microscope-assisted decompressive surgery in the lumbar spine. In this study, we summarized our clinical results in 230 consecutive patients treated for lumbar disc herniations, lumbar spinal stenosis, and lumbar facet joint cysts.…”
Section: Discussionmentioning
confidence: 99%
“…20 In contrast, 2 small randomized controlled trials showed shorter hospital stay for patients treated with tubular microdiscectomy. 17,25 In the short term (8 weeks), there was no difference in RDQ or VAS scores in the study by Arts et al 4 Likewise, there were similar rates of complete recovery and time to complete recovery. During recovery, VAS leg and back and RDQ scores were slightly higher in the tubular group compared with the standard group.…”
Section: Perioperative Short-term and Long-term Outcomes Of Tubularmentioning
confidence: 88%
“…17,25,29 In contrast, the trial conducted by Ryang et al demonstrated no difference in operating times. 26 Multiple retrospective studies and a meta-analysis support similar operating times for the tubular and standard groups.…”
Section: Operative Considerations and Complications Of Tubular Discecmentioning
confidence: 90%
See 1 more Smart Citation
“…Huang et al [4] found that C-reactive protein and interleukin-6 levels were lower in the endoscopic group, suggesting that, with comparable clinical results, the lower systemic insult with minimally invasive surgery may justify its use.…”
Section: "There Is No Such Thing As Darkness Just the Absence Of Ligmentioning
confidence: 95%